Allure Enterprise / Syed Azaharie Wan Long. - Wan Long, Syed Azaharie; Mohd Rasit, Mohd. Hairi; Mohd. Yusof, Mohd. Farid; Zainullah, Nik Nordiana; Dollah, Nor Haidawati (2003)
Our company, Allure Enterprise created in July 2003. Allure Enterprise is a company that supplies hair care products to salons and individual. Our business begin operating on 1st January.2004 Our location is at : No. G02. Ground Floor Plaza Alam Sentral, Shah Alam 40000 Shah Alam Selangor Darul Ehsan The reason why we choose this location is its strategic, privacy, famous and easy to reach by our target market. In Shah Alam, there are many salons but most of them buy their products from suppliers in Subang Jaya, Kuala Lumpur and Klang. Thus,it gives the idea to start this type of business. Our objective is to supply hair care products to al salons in Shah Alam because it has a lot of demands on this product. This type of business will get good feedback from the customers because there is only one supplier in hair care products nearer to them and offers variety of quality hair care products. Allure Enterprise has 5 partners and each of the partner had contributed 20% and made a loan from Skim Pembiayaan Kecil MARA 80% of our business capitalLastly, we confident that our company, Allure Enterprise can earn profit and we plan to have a branch in other place some other time. We hope that our company will run smoothly and get a good feedback from customer.